THE PROSPECTIVE APPLICATION OF PRE-CAST AND PRE-STRESSED CONCRETE STRUCTURES IN MALAYSIA - YAAKOP, ZAHARA (Universiti Teknologi PETRONAS, 2007)
1bis final year project is titled 'The prospective application of pre-cast and prestressed concrete structures in Malaysia. The main objective of this project is to introduce to the Malaysian building industry the advantages and disadvantages of precast and pre-stressed concrete structures in replacing the traditional cast in-situ structures. 1bis project is basically proposed because of the current problems with the construction industry in Malaysia which consist of delays in schedule, poor quality of end products and labor problems. Pre-cast and pre-stressed concrete structures are proposed because of its usefulness and as an alternative for the execution of construction projects which needed to be done in the shorter period of time and with a high concern for the quality: